Spatial heterogeneity of the lithospheric destruction of the North China Craton: Evidence from an extended magnetotelluric sounding profile - Ji, Leizhe; Ye, Gaofeng; Jin, Sheng; Ma, Xingzhi; Wei, Wenbo; Wang, Shuo; Qi, Jialin; Lei, Qing; Gu, Jiangfan (Frontiers in Earth Science, 2023)
To study the spatial heterogeneity of the North China Craton (NCC) destruction, this paper used a magnetotelluric sounding (MT) profile that passes through almost the entire NCC from west to east. Three-dimensional inversion is used to obtain a lithospheric resistivity model of the NCC. The results show that the upper crust of the Ordos Block is characterized by high resistivity. The lower crust to the upper mantle is characterized by low resistivity. The resistivity structure below the Trans-North China Orogen (TNCO) has stratification features; The Shanxi Graben shows high-low-high-low resistivity features from the upper crust to the asthenosphere; The lithosphere of the Lüliang and Taihang uplifts show high-resistivity features, and only some local relatively low-resistivity areas appear at the crust-mantle boundary. The upper crust on both sides of the Tan-Lu Fault Zone is characterized by high resistivity, but the resistivity structures of the lower crust and the lithospheric mantle are significantly different; The lower crust and the lithospheric mantle of the Sulu Orogenic Belt on the east are characterized by high resistivity; The Luxi Uplift on the west is represented by low resistivity. We propose that the mantle low-resistivity bodies (C1 and C4) of the Western and Eastern blocks may be related to the upwelling of partial melting materials along the ancient structurally weak zones in the lithosphere. The TNCO still has a typical Archean cratonic lithosphere, and the low-resistivity body C2 may be the remnant of the subducted oceanic crust. The Tan-Lu Fault Zone is structurally weak in the Eastern Block, while its western branch is a channel for the asthenospheric upwelling. We propose that the lithosphere of the northwestern Ordos Block and the Yinchuan-Hetao area is being destructed, and the TNCO is in the initial stage of being destructed. In contrast, the lithosphere of the Eastern Block has been severely destructed. In conclusion, affected by the subduction of the paleo-Pacific plate and the collision of the Indian and Eurasian plates, the ancient structures in the NCC were reactivated in the Mesozoic and Cenozoic, resulting in the spatial heterogeneity of the NCC destruction.